2007
DOI: 10.1124/dmd.107.018044
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Resistance Protein 1 Limits Fetal Distribution of Nitrofurantoin in the Pregnant Mouse

Abstract: ABSTRACT:The efflux transporter, the breast cancer resistance protein (BCRP), is most abundantly expressed in the apical membrane of the placental syncytiotrophoblasts, indicating that it could play an important role in protecting the fetus by limiting xenobiotic/drug penetration across the placental barrier. In the present study, we examined whether Bcrp1, the murine homolog of human BCRP, . These results clearly suggest that Bcrp1 significantly limits fetal distribution of NFT in the pregnant mouse, but has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 32 publications
4
51
1
Order By: Relevance
“…In the placenta, BCRP is located on the apical membrane of syncytiotrophoblasts that faces the maternal blood (Maliepaard et al, 2001), implicating its role in limiting fetal exposure to drugs and xenobiotics by pumping them from the fetal compartment back to the maternal circulation. In vivo studies using Bcrp1 knockout mice have indeed shown that Bcrp1, the murine homolog of human BCRP, significantly limits fetal exposure to certain BCRP substrates including glyburide, nitrofurantoin, and topotecan (Jonker et al, 2000;Zhang et al, 2007;Zhou et al, 2008). Results from placenta perfusion studies support the same conclusion (Kraemer et al, 2006;Staud et al, 2006).…”
Section: Introductionsupporting
confidence: 74%
“…In the placenta, BCRP is located on the apical membrane of syncytiotrophoblasts that faces the maternal blood (Maliepaard et al, 2001), implicating its role in limiting fetal exposure to drugs and xenobiotics by pumping them from the fetal compartment back to the maternal circulation. In vivo studies using Bcrp1 knockout mice have indeed shown that Bcrp1, the murine homolog of human BCRP, significantly limits fetal exposure to certain BCRP substrates including glyburide, nitrofurantoin, and topotecan (Jonker et al, 2000;Zhang et al, 2007;Zhou et al, 2008). Results from placenta perfusion studies support the same conclusion (Kraemer et al, 2006;Staud et al, 2006).…”
Section: Introductionsupporting
confidence: 74%
“…In support of this, glyburide concentrations are higher in Bcrp-null fetuses compared with wild type (Zhou et al, 2008b). Likewise, the concentration of the antibiotic nitrofurantoin is elevated 5-fold in fetuses from Bcrp-null mice (Zhang et al, 2007c). These findings are of interest because glyburide and nitrofurantoin are routinely prescribed for pregnant patients for the treatment of gestational diabetes and urinary tract infections, respectively.…”
mentioning
confidence: 53%
“…We found that fetal exposure (fetal-to-maternal plasma AUC ratios) to nitrofurantoin and glyburide in Bcrp1-knockout mice was increased ∼five-and twofold, respectively, compared to those in wild-type mice (35,113). The role of BCRP in determining fetal exposure to drugs and xenobiotics can also be studied using other methods such as human placenta perfusion, and this topic has been extensively reviewed elsewhere (114).…”
Section: Tissue Localization and Role In Drug Dispositionmentioning
confidence: 98%